BAHAN AJAR MULTI-INTELEGENSIA BERBASIS ANIMASI SEBAGAI MEDIA UNTUK MENINGKATKAN PRESTASI DAN MOTIVASI BELAJAR MAHASISWA TADRIS KIMIA IAIN WALISONGO SEMARANG (Universitas Negeri Semarang, 2013)
A study concerning the application of multi-intelligence teaching materials based animation to improve student achievement and student motivation in Chemistry Tadris IAIN Walisongo Semarang on the material structure of the metal packing have been observed. Research using cluster random sampling technique. The samples were divided into experimental class (a class that uses animation-based learning media) and control classes (classes that do not use animation-based learning media). Data analysis showed that there were significant differences between the experimental class and the control class. On the one hand the test calculations obtained t count less than t table with dk = 20 with  = 5%, then we can conclude that Ha is accepted, which means that the average student learning outcomes using media-based learning animation (the experimental group) was better than average of chemistry student learning outcomes that do not use the animation (the control group). As well as in the assessment of the affective aspects. Students who get the lesson with animated media proved to have the learning motivation better than students who do not use animation media. Therefore it can be concluded that the animationbased learning media is effective to improve student achievement and student learning motivation.Keywords: Multi-intelligence Animation-based